2006
DOI: 10.1128/iai.74.1.781-785.2006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Escherichia coli Asymptomatic Bacteriuria Strain 83972: the Taming of a Pathogen

Abstract: Escherichia coli 83972 is a clinical asymptomatia bacteriuric isolate that is able to colonize the human urinary bladder without inducing an immune response. Here we demonstrate that one of the mechanisms by which this strain has become attenuated is through the mutation of its genes encoding type 1 and P fimbriae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
127
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(130 citation statements)
references
References 39 publications
1
127
1
1
Order By: Relevance
“…E. coli strains belonging to group B2 are associated with pyelonephritis and other extraintestinal invasive clinical syndromes, such as bacteremia, prostatitis, and meningitis. Also, we recently characterized the fim, pap, and foc gene clusters of the strain and showed that although the fimbriae encoded by these clusters are nonfunctional, the strain contains sequence information that bears witness of a pathogenic past (26,41). Thus, the fimH allele of 83972 encodes minor amino acid variations (compared with the K-12 version) that are consistent with those of previously characterized pyelonephritis isolates (51)(52)(53).…”
supporting
confidence: 55%
“…E. coli strains belonging to group B2 are associated with pyelonephritis and other extraintestinal invasive clinical syndromes, such as bacteremia, prostatitis, and meningitis. Also, we recently characterized the fim, pap, and foc gene clusters of the strain and showed that although the fimbriae encoded by these clusters are nonfunctional, the strain contains sequence information that bears witness of a pathogenic past (26,41). Thus, the fimH allele of 83972 encodes minor amino acid variations (compared with the K-12 version) that are consistent with those of previously characterized pyelonephritis isolates (51)(52)(53).…”
supporting
confidence: 55%
“…In this regard, Svanborg and colleagues have recently proposed an interesting mechanism to explain the occurrence of ASB where Toll-like receptor 4 (TLR4) controls the initial mucosal response to UPEC, suggesting that the development of symptomatic infection would be more closely associated with variation of the host environment than with expression of bacterial VFs, since TLR4 mutant mice develop an asymptomatic carrier state resembling human ASB (20). They have shown that a clinical ASB-associated strain, E. coli 83972, is able to colonize the human urinary bladder without inducing an immune response, through the mutation of its genes encoding type 1 and P fimbriae (14). Thus, the development of symptomatic infection may be more closely associated with the variation in the host environment than the virulence of the microorganisms.…”
mentioning
confidence: 99%
“…Microorganisms use various mechanisms to acquire drug resistance viz. horizontal gene transfer through plasmid, transposons and bacteriophage, recombination of foreign DNA in bacterial chromosome, and mutation in different chromosomal locus (Klemm et al, 2006). Brown et al (2003) have reported that the horizontal gene transfer is the factor in occurrence of antibiotic resistance in clinical isolates and suggested that the high prevalence of resistance to a particular antibiotic does not always reflect antibiotic consumption as suggested by Nwanze et al (2007).…”
Section: Mechanism Of Microbial Resistance Towards Antimicrobial Agentmentioning
confidence: 95%